Monitoring of Students` Professional Merits at the University - Sofjina, Vera; Gribanova, Diana; Melenevskaja, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Constant system of monitoring of students` professionals merits is an effective instrument of quality evaluation in higher education. Different approaches to understanding of professional merits are considered in the article. The main professional merits are defined for professionals in the field of international relations. Results of monitoring of students` professional merits are described from first to fifth courses of international relations department. The second research is aimed to the professional merits of future teachers-students. The research demonstrates that the educational environment of university and especially designed and approved program of development of professional merits are important for formation of students` professional competence.